Analysis of end-To-end delay characteristics for various packets in IEC 61850 substation communications system - Das, N.; Ma, W.; Islam, Syed (2015)
© 2015 IEEE. Substation plays an important role in power system communications for safe and reliable operation of entire power networks. Substation communication networks are connected with various substation intelligent electronic devices (IEDs), which is substation systems lifeblood and the system availability is decided by its real-Time performance. International Electro-Technical Commission (IEC) has been developed the standards based on object-oriented technologies for substation automation. IEC 61850 protocol has been applied widely in substation communication applications. It presents new challenges to realtime performance simulation and testing of protective relays. In this paper, an optimized network engineering tool (OPNET) or Riverbed modeler simulation tool/ software has been used for the modeling of IED in substation level network. Based on the simulation results, different types of data stream have been discussed, such as, periodic data stream, random data stream and burst data steam. The typical studies using these models, to construct substation automation system (SAS) network on the OPNET modeler or Riverbed modeler was made to reveal the impact of each affecting parameter or factor to the real-Time performance of substation communications system, which is also incorporated in this report.